First quantitative dosages: Strong correlations between non-5-HT2Rs serotonin receptors on normal human heart valves - Schussler, Olivier; Maroteaux, Luc; Jashari, Ramadan; Falcoz, Pierre; Alifano, Marco; Lecarpentier, Yves; Launay, Jean-Marie (Frontiers in Cardiovascular Medicine, 2022)
Objectives Although critical in animal and human development and pathology, a measurement of the quantitative expression of 5-HTR serotonin receptors on animal or human valvular tissues has never been performed. Methods Quantification of the most frequent 5-HTRs reported as being present in human peripheral tissue was performed using radiolabeled agonists/antagonists. A membrane protein extract from normal human valves (aortic/mitral/tricuspid and some pulmonary) and associated diseased left myocardium, all unusable in clinics, were obtained from the Homograft bank. Results We analyzed 5-HT1AR/5-HT1B/DR/5-HT2AR/5-HT2BR/5-HT 2CR/5-HT4R/5-HT7R from 28 hearts. We confirmed the presence of tissue and measured the quantitative content for respective proteins in femtomol/mg of protein extracts: for 5-HT2AR (35.9+/−0.7), 5-HT2BR (28.8+/−1.3) but also a newly observed and robust expression for 5-HT4R (38+/−4.2). We identified one, 5-HT1ARs (4.9+/−0.3), and the possible expression, but at a very low level, of previously reported 5-HT1B/DRs (1.3+/−0.5) as well as the new 5-HT7Rs (3.5+/0.1) and 5-HT2CRs (1.2+/−0.1). Interestingly, by using univariate analysis, we were able to observe many correlations between the different 5-HTR levels of expression especially between 5-HT1AR/5-HT1B/DR and also between 5-HT4R/5-HT7R, but none were observed between 5-HT2AR and 5-HT2BR. Using multivariate analyses for a specific 5-HTR level of expression, after adjustment for implantation sites and other 5-HTRs, we found that 5-HT1AR was correlated with 5-HT1B/DR;5-HT4R with 5-HT7R and 5-HT1AR;5-HT2BR with 5-HT2AR only. For 5-HT2C, no correlation was observed. Conclusion 5-HT2AR/5-HT2BR and 5-HT4R were all observed to have a high and equal level of expression on human valves, but that of 5-HT1AR was more limited. Since these non-5-HT2Rs are coupled with different G-proteins, with specific signaling, theoretically they may control the main 5-HT2R signaling (i.e., PLC/DAG-PKC-ERK/Ras/Src signaling) involved in valvular fibrosis and degeneration.